A computational study on the optical shaping of gas targets via blast wave collisions for magnetic vortex acceleration. (13th July 2022) - Tazes, I.; Passalidis, S.; Kaselouris, E.; Fitilis, I.; Bakarezos, M.; Papadogiannis, N. A.; Tatarakis, M.; Dimitriou, V.
Abstract: This research work emphasizes the capability of delivering optically shaped targets through the interaction of nanosecond laser pulses with high-density gas-jet profiles, and explores proton acceleration in the near-critical density regime via magnetic vortex acceleration (MVA). Multiple blast waves (BWs) are generated by laser pulses that compress the gas-jet into near-critical steep gradient slabs of a few micrometres thickness. Geometrical alternatives for delivering the laser pulses into the gas target are explored to efficiently control the characteristics of the density profile. The shock front collisions of the generated BWs are computationally studied by 3D magnetohydrodynamic simulations. The efficiency of the proposed target shaping method for MVA is demonstrated for TW-class lasers by a particle-in-cell simulation.